Bentuk Hubungan Hukum Para Pihak dan Tanggung Jawab Agen Dalam Penyelenggaraan Branchless Banking di Indonesia - Inda - Rahadiyan; M. Alif Akbar Pranagara (Jurnal Hukum IUS QUIA IUSTUM, 2017)
The problems of this research included: first, how is the legal relationship between parties on the implementation of Branchless Banking in Indonesia? Second, how is the legal responsibility of an agent on the implementation of Branchless Banking in Indonesia? This research is conducted using normative legal method supported by empirical data. The findings show that the legal relationship between agent and bank on the Branchless Banking mechanism different from the legal relationship between an agent and its principal based on the agency agreement. The legal responsibility of an agent on the implementation of Branchless Banking also has the different concept from the legal responsibility of an agent based on the agency agreement.